2007
DOI: 10.1308/135576107780556789
|View full text |Cite
|
Sign up to set email alerts
|

Reply Letters following Orthodontic Consultations: An Audit of Merseyside General Dental Practitioners’ Satisfaction

Abstract: This audit provides evidence that GDPs consider that a significant portion of the information in consultants' reply letters is not needed. Relevant information may be poorly communicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…9 As brevity is preferred, PHC doctors prefer summaries instead of free text, and information on management plans is considered more important than examination findings, which specialists consider essential. 10 Consultants and doctors in training also have different perspectives from which they judge referral letters. It was found that consultants considered the disciplinary context, was more collegial and flexible and valued the sharing of roles and networking more than did the doctors in training, who were less flexible and insisted on more exact communication.…”
Section: • Factors Concerning Referralmentioning
confidence: 99%
“…9 As brevity is preferred, PHC doctors prefer summaries instead of free text, and information on management plans is considered more important than examination findings, which specialists consider essential. 10 Consultants and doctors in training also have different perspectives from which they judge referral letters. It was found that consultants considered the disciplinary context, was more collegial and flexible and valued the sharing of roles and networking more than did the doctors in training, who were less flexible and insisted on more exact communication.…”
Section: • Factors Concerning Referralmentioning
confidence: 99%